2021
DOI: 10.1097/01.ogx.0000802680.45004.84
|View full text |Cite
|
Sign up to set email alerts
|

Association of Chemotherapy Timing in Pregnancy With Congenital Malformation

Abstract: The following full text is a publisher's version.For additional information about this publication click this link. https://repository.ubn.ru.nl/handle/2066/234977Please be advised that this information was generated on 2022-01-10 and may be subject to change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…A study of 755 pregnant women with cancer found that the occurrence of major congenital malformations was highest when the first chemotherapy cycle was initiated before 12 weeks of gestation. 29 In our study, women hospitalised for cancer treatment in the first trimester tended to have a greater risk of birth defects than patients treated for malignancies later on.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…A study of 755 pregnant women with cancer found that the occurrence of major congenital malformations was highest when the first chemotherapy cycle was initiated before 12 weeks of gestation. 29 In our study, women hospitalised for cancer treatment in the first trimester tended to have a greater risk of birth defects than patients treated for malignancies later on.…”
Section: Discussionmentioning
confidence: 54%
“…Findings for prepregnancy cancer contrast with the more apparent association between cancer during pregnancy and birth defects. The literature remains mixed on these associations 24–30 . A registry of 231 women with cancer during pregnancy found that 3.8% of patients had offspring with birth defects, essentially equivalent to the rate in the general population 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemotherapy and resulting metabolites may be detected in semen and vaginal secretions after administration [48–52]. Moreover, a recent study found that chemotherapy was associated with an increased risk of major congenital malformations in the first 12 weeks of pregnancy [53 ▪▪ ].…”
Section: Addressing Sexual Dysfunction In Adolescent and Young Adult ...mentioning
confidence: 99%
“…In addition, her physicians have counseled her that she would most likely require postoperative chemotherapy, which is associated with an increased risk of induced congenital malformations. 1 The first decision she makes is to end the pregnancy. The patient's grief related to the cancer diagnosis and the decision to end the pregnancy is incalculable.…”
mentioning
confidence: 99%